Exploring The Correlation between EFL Students’ Information Literacy and Media Literacy in Evaluating Hoax News - Aisyah, Sitti Nur; Tungka, Novalita Fransisca (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
<!–StartFragment–><span lang="EN" style="font-size: 10.0pt; line-height: 115%; font-family: ’Calibri’,sans-serif; mso-fareast-font-family: Calibri; mso-bidi-font-family: Calibri; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This research aims to explore the correlation between EFL students’ information literacy and media literacy in evaluating hoax news. The subjects of this research were 101 EFL students in the 2021–2024 batch. This research used a quantitative approach with data collection techniques through questionnaires and reading test distributed online using Google Form. The results of the research showed that in the first hypothesis there was no significant correlation between information literacy and students’ ability to evaluate hoax news, which means the null hypothesis was accepted. In the second hypothesis, it was shown that there was a significant correlation between media literacy and students’ ability to evaluate hoax news, nevertheless the relationship was very weak, which means the alternative hypothesis was accepted. While in the third hypothesis, there was no significant correlation between information literacy and media literacy on students’ ability to evaluate hoax news. These findings indicate that media literacy has a weak correlation in the context of hoax news evaluation by EFL students at Sintuwu Maroso University. <!–EndFragment–>